Effect of forest disturbance on myxomycete assemblages in the southwestern Peruvian Amazon - Rojas Alvarado, Carlos Alonso (2012)
Although the effects of microenvironmental factors on distribution patterns in myxomycetes have been investigated, studies of the responses of this group of organisms to different regimes of forest disturbance are relatively few in number. In an effort to understand the implications of forest fragmentation and habitat loss on myxomycetes, the project described herein was carried out at the Los Amigos Biological Station in southeastern Peru. The structure and composition of assemblages of myxomycetes were investigated in relation to three different forest types and climatic periods in the area of study. An analysis of the most commonly recorded substrates was carried out as well. The results suggested that habitat loss, through differences in forest structure, was the factor determining most of the differences in fruiting body abundance of myxomycetes among forest types. In addition, a switch in the ecological strategy of dispersal seemed to be an important factor accounting for differences in the fruiting body abundance and structure of assemblages of myxomycetes between collecting periods. This study provides evidence indicating that for microbial assemblages to maintain the balance of functional interactions within a particular forest ecosystem, the conservation of the forests themselves should be considered